2002
DOI: 10.1074/jbc.m108702200
|View full text |Cite
|
Sign up to set email alerts
|

SYT Associates with Human SNF/SWI Complexes and the C-terminal Region of Its Fusion Partner SSX1 Targets Histones

Abstract: A global transcriptional co-activator, the SNF/SWI complex, has been characterized as a chromatin remodeling factor that enhances accessibility of the transcriptional machinery to DNA within a repressive chromatin structure. On the other hand, mutations in some human SNF/SWI complex components have been linked to tumor formation. We show here that SYT, a partner protein generating the synovial sarcoma fusion protein SYT-SSX, associates with native human SNF/SWI complexes. The SYT protein has a unique QPGY doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 88 publications
4
83
0
1
Order By: Relevance
“…6 In fact, SYT has been shown to bind to hBRM/hSNF2a, a major component of the SWI/SNFtype chromatin remodeling complex. 5,[7][8][9] Moreover, it was also shown that SYT interacts with the putative transcriptional factor AF10, histone acetyl transferase p300 and a component of histone deacetylase complex mSin3A. [10][11][12] Thus, it is possible that SYT regulates transcription through the binding to chromatin modifiers.…”
mentioning
confidence: 99%
“…6 In fact, SYT has been shown to bind to hBRM/hSNF2a, a major component of the SWI/SNFtype chromatin remodeling complex. 5,[7][8][9] Moreover, it was also shown that SYT interacts with the putative transcriptional factor AF10, histone acetyl transferase p300 and a component of histone deacetylase complex mSin3A. [10][11][12] Thus, it is possible that SYT regulates transcription through the binding to chromatin modifiers.…”
mentioning
confidence: 99%
“…Several reports have localized the SYT/SSX fusion protein to the nucleus and described its role in the regulation of chromatin remodelling. 20,21 Various groups have recently found mutations in the EGFR tyrosine kinase domain (exons 18-21) in non-small-cell lung carcinoma that sensitize tumor cells to the effects of gefitinib and appear to be associated with clinical responsiveness to this drug. The prevalence of missense mutations in these carcinomas varies from 20 to 40% in Asian countries (Taiwan, Korea, and Japan) to about 10% in non-east Asians.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the transcriptional repressor function(s) of the SSX proteins, PcG proteins form multi-protein complexes that maintain the repressed state of target genes by inducing changes in chromatin structure (Schuettengruber et al, 2007;Schwartz and Pirrotta, 2007). Through cellular colocalization studies, we and others have found that the SSXRD is responsible for (i) SSX nuclear localization, (ii) colocalization with PcG proteins, (iii) association with mitotic chromosomes, and (iv) association with core histones (dos Santos et al, 2000a;Kato et al, 2002). Through yeast two-hybrid screening, we have previously identified the SSX2IP (also known as ADIP) and RAB3IP proteins as in vivo interactors of the SSX KRAB-like domain .…”
Section: Introductionmentioning
confidence: 94%
“…Of these, the SNH domain directly interacts with the acute leukemia-associated transcription factor AF10 (de Bruijn et al, 2001a), the SWI/SNF ATPases BRM and BRG1 (Thaete et al, 1999;Perani et al, 2003;de Bruijn et al, 2006), the histone acetyltransferase p300 (Eid et al, 2000) and the corepressor mSin3A (Ito et al, 2004). Indirectly, the SS18 protein associates with yet another SWI/SNF protein, INI1 (Debernardi et al, 2002;Kato et al, 2002). The QPGY domain is a transcriptional coactivation domain and mediates multimerization of the SS18 protein (Brett et al, 1997;Thaete et al, 1999;Perani et al, 2003).…”
Section: Introductionmentioning
confidence: 99%